1992
DOI: 10.1085/jgp.99.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Intramembrane charge movements in frog skeletal muscle in strongly hypertonic solutions.

Abstract: Intramembrane charge movements were studied in intact, voltageclamped frog (Rana temporaria) skeletal muscle fibers in external solutions made increasingly hypertonic by addition of sucrose. The marked dependence of membrane capacitance on test potential persisted with increases in extracellnlar sucrose concentration between 350 and 500 mM. Charge movements continued to show distinguishable early monotonic (qa) decays and the strongly voltage-dependent delayed (qv) charging phases reported on earlier occasions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Muscles were initially bathed in isotonic Ringer solution; this was replaced by 500 m m sucrose‐Ringer for 10 min before the application of the experimental solutions, all of which also contained 500 m m sucrose in order to suppress mechanical activity. At such concentrations, sucrose has been shown to suppress mechanical activity (Caputo, 1968) whilst permitting both transitions in intramembrane charge (Huang, 1992) and cytosolic Ca 2+ transients in response to applied depolarization (Parker & Zhu, 1987) as was also apparent in the present experiments.…”
Section: Methodssupporting
confidence: 78%
“…Muscles were initially bathed in isotonic Ringer solution; this was replaced by 500 m m sucrose‐Ringer for 10 min before the application of the experimental solutions, all of which also contained 500 m m sucrose in order to suppress mechanical activity. At such concentrations, sucrose has been shown to suppress mechanical activity (Caputo, 1968) whilst permitting both transitions in intramembrane charge (Huang, 1992) and cytosolic Ca 2+ transients in response to applied depolarization (Parker & Zhu, 1987) as was also apparent in the present experiments.…”
Section: Methodssupporting
confidence: 78%
“…Electrical recordings were made at 2-4 'C in either of two bathing solutions. Both have been used in earlier work (Huang, 1991(Huang, , 1992. The Ca2+-containing solution consisted of 80 mm tetraethylammonium sulphate, 15 mm tetraethylammonium chloride, 2-5 mm Rb2SO4, 8 mM CaSO4, 500 mm sucrose and 3 mm N-2-hydroxyethylpiperazine-N'-2-ethanesulphonic acid (Hepes).…”
Section: Charge Inactivation In Musclementioning
confidence: 99%
“…Thirdly, repeated control runs were interposed within sequences of obtaining five test averages to monitor the consistency of fibre cable constants. Values of specific membrane constants computed directly from successive control records could thus be scrutinized to assess fibre condition and stability (see Huang, 1991Huang, , 1992. Their values at the beginning, and at the end of each run are provided in the figure legends.…”
Section: Capacitative Charge In Test and Control Voltage Stepsmentioning
confidence: 99%
“…However, at higher osmolalities, a reduction in the amount of Ca2+ released by depolarization probably contributes to the inhibition of the force responses (Parker & Zhu, 1987), although it is not clear whether this reduction in release results from depolarization being less able to open the Ca2+ release channels or from some initial translocation of Ca2+ causing partial depletion of the SR. Recently, Huang (1992) has shown that strongly hypertonic solutions abolish the delayed component of asymmetric charge movement (q,), but it is not certain whether the suppression of q, at such high tonicity is the result, or the cause, of reduced Ca2+ release.…”
Section: Introductionmentioning
confidence: 99%